ENHANCING FINANCIAL LITERACY AMONG ELEMENTARY SCHOOL STUDENTS THROUGH A SCHOOL-BASED FINANCIAL EDUCATION PROGRAM - Krishna Prafidya Romantica (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service program was carried out at SDN Pengasinan 1, Depok, with the aim of instilling financial literacy in elementary school students from an early age. The activities were designed to be contextual and engaging, including storytelling, saving simulations, the use of activity books and educational piggy banks, as well as a modified Monopoly game. This participatory approach enabled students not only to understand basic financial concepts, but also to practice them in daily life. Interviews with students revealed high enthusiasm; they expressed enjoyment in receiving piggy banks and activity books and acknowledged the importance of saving and managing pocket money. Questionnaire results further indicated that most students strongly agreed the materials were clear, relevant, and beneficial. Overall, the program successfully enhanced students’ financial awareness, encouraged saving habits, and provided practical tools to support responsible money management.